1993
DOI: 10.1103/physrevb.47.967
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in Josephson-junction arrays with long-range interaction

Abstract: We theoretically investigate ordered and disordered Josephson-junction arrays with long-range interaction. These arrays consist of two orthogonal sets of N parallel superconducting wires that are Josephson coupled to each other at every point of crossing. In this configuration, all wires, regardless of spatial separation, are nearest-or next-nearest neighbors. Using a mean-field approximation we show that the arrays undergo a phase transition to a macroscopically phase-coherent state at a temperature T, =NEJ/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
3
12
1
Order By: Relevance
“…The critical current is linear in N for small N, but saturates at a finite value for large N. The saturation value varies as the inverse square root of wire inductance per unit length. This is in excellent agreement with a simple model suggested by Sohn et al, 3,4 and the occurrence of saturation is also confirmed experimentally. 3,4 We also find that our numerical current-voltage (IV) characteristics are hysteretic, even though the array, in our model, is composed entirely of nonhysteretic elements.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The critical current is linear in N for small N, but saturates at a finite value for large N. The saturation value varies as the inverse square root of wire inductance per unit length. This is in excellent agreement with a simple model suggested by Sohn et al, 3,4 and the occurrence of saturation is also confirmed experimentally. 3,4 We also find that our numerical current-voltage (IV) characteristics are hysteretic, even though the array, in our model, is composed entirely of nonhysteretic elements.…”
Section: Introductionsupporting
confidence: 91%
“…For this reason, such arrays are sometimes said to have long-range interactions. Arrays of this kind were, to the best of our knowledge, first studied theoretically by Vinokur et al 2 They have since been fabricated and studied both experimentally and theoretically by Sohn et al 3,4 In the presence of a magnetic field, it has been predicted that such long-range interactions, even in periodic arrays, will give rise to glassy behavior. 2,5,6 Other types of hybrid arrays can readily be imagined.…”
Section: Introductionmentioning
confidence: 99%
“…Although such arrays had been fabricated by Sohn et al [2], the samples used in the present Letter for the first time have low enough critical currents and hence low enough screening to be in the regime well described by existing theoretical models [3,4].…”
Section: Department Of Physics and Division Of Engineering And Appliementioning
confidence: 91%
“…For an ordered array with long-range interaction in the limit of negligible screening, Sohn et al [3] have performed a mean-field analysis and computed the transition temperature T MF c ͑ f͒ as a function of the applied field and array size. Because each wire has a large number of nearest neighbors, a mean-field theory using the phase of each wire as a classical thermodynamic variable should provide a good description of this system.…”
Section: Department Of Physics and Division Of Engineering And Appliementioning
confidence: 99%
“…2 The supercurrent transport and magnetic screening response of such proximity coupled Josephson-junction ͑JJ͒ ensembles, ordered or otherwise, have been studied extensively. [3][4][5][6][7][8] In absence of magnetic fields, coupled JJs in two-dimension ͑2D͒ approach zero resistance state via Kosterlitz-Thouless ͑KT͒ transition 9 at T KT . Increasing the temperature above T KT , dissociates the vortex-antivortex bound pairs and the resultant increase in entropy leads to some finite resistance.…”
Section: Introductionmentioning
confidence: 99%